1999
DOI: 10.1002/(sici)1097-4547(19991101)58:3<442::aid-jnr10>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Mexiletine and magnesium independently, but not combined, protect against permanent focal cerebral ischemia in Wistar rats

Abstract: The neuroprotective effect of mexiletine (Mex), a potent Na(+) channel blocker which decreases neuronal energy demands and prevents energy depletion during ischemia, was evaluated in Wistar rats subjected to permanent middle cerebral artery (MCA) occlusion. Postmortem infarct volumes were determined by quantitative image analysis of triphenyltetrazolium (TTC)-stained brain sections. Pretreatment with Mex resulted in a significant infarct volume reduction when administered intraperitoneally, either at the dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 0 publications
2
14
1
Order By: Relevance
“…Magnesium, the second most common intracellular cation and the most abundant intracellular divalent cation (32)(33)(34), has been shown to be neuroprotective in several experimental models of ischemic and excitotoxic brain injury (20,21). However, other studies have failed to detect a neuroprotective effect of magnesium (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium, the second most common intracellular cation and the most abundant intracellular divalent cation (32)(33)(34), has been shown to be neuroprotective in several experimental models of ischemic and excitotoxic brain injury (20,21). However, other studies have failed to detect a neuroprotective effect of magnesium (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Almost one-quarter of magnesium studies (6 of 26) showed a worsening of infarct size. Furthermore, magnesium was not effective when combined with mexiletine (Lee et al, 1999). The use All, all treatment groups in the experiment; C, control group; Com, combination treatment group (magnesium, melatonin, and minocycline); M, mean; Mel, melatonin group; N, number of animals.…”
Section: Explanation 1: Failure Attributable To Lack Of Drug Efficacymentioning
confidence: 99%
“…It has also been proposed that the systemic adverse effects caused by NMDA antagonists may be greatly reduced and neuroprotective efficacy greatly enhanced, when Mg ϩϩ is adminis-tered directly via a proximal intraarterial infusion into the target organ. 13,20 Magnesium ion can readily cross the blood-brain barrier to bind specific receptors in the brain. 8,9 It prevents excitotoxicity in blocking various subtypes of Ca ϩϩ and NMDA channels and has proved to be neuroprotective in vitro and in vivo.…”
mentioning
confidence: 99%
“…18 Alternatively, we have shown that pretreatment with Mg ϩϩ protects the brain against permanent focal cerebral ischemia. 13 In a delayed treatment paradigm, intravenous administration of Mg ϩϩ was shown in rats to offer a window of opportunity that extends up to 6 hours following embolic stroke, a model closer to permanent focal cerebral ischemia. 43 Taken together, it is evident that Mg ϩϩ has the ability to modulate cerebral bioenergetics during ischemia-reperfusion and, therefore, offers neuroprotection against both permanent and transient focal cerebral ischemia.…”
mentioning
confidence: 99%